Kawiryan Discourse as The Legitimacy of The Islamic Sultanate in Serat Saptastha - Afiliasi Ilafi; Supana Supana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2018)
The purpose of writing this article is to analyze the discourse of heroism ( kawiryan ) according to Sultan Hamengkubuwana VII contained in the Serat Saptstha manuscript. It is a type of historical manuscript that provides an overview about the discourse stored in the content of the manuscript. The Sultan discussed in this article is Hamengkubuwana VII. He is an Islamic Sultan who ruled the societies in 1877-1921. His reign is in Keraton Ngayogyakarta (Ngayogyakarta Palace) and it is a kind of Islamic Sultanate. Based on the conclusion of this study, Hamengkubuwana VII as the King sent by God performed an image as a very humble sultan. The legitimacy of his power promotes an understanding of Islamic Sultanate represented by Hamengkubuwana VII. The representation of peaceful and serene life portrayed by Hamengkubuwana VII makes the image of Hamengkubuwana VII to be an irreplaceable sultan and his personality also inspires the societies in terms of the importance to always remember The Creator or on the other word is God.